ANALISIS LAHAN OPTIMUM YANG LAYAK DALAM USAHA TANI RUMAH TANGGA PETANI PADI DI SULAWESI SELATAN - Misbahuddin Misbahuddin (Jurnal Bisnis dan Kewirausahaan, 2015)
This study aimed to analyze the determination of the optimum land, labor, consumption and exchange rate rice farmers and analyze the impact of the amount of production, the selling price, the amount of labor and economic aspects of business-to-income rice farmers and analyze the level of prosperity, economic factors and physical factors land in the five district and formulate strategies what is right for improving the welfare of rice farmers in South Sulawesi. This study uses survey data of 400 respondents rice farmers. Analyzer used to calculate the optimum land, labor income families as well as the production capacity is to use the model Z score, while using SWOT strategy formulation. The findings of this study were obtained land is optimum for a decent life is 0:55 ha/person for the technical irrigation (the owner and tenants) and 0.99 ha / person for rainfed (owner and tenants). rainfed amounted to 0.99 ha. For these types of farmers as owners or tenants alone, optimum land area is 1.10 ha/person for technical irrigated rice. As for the types of rainfed rice amounted to 1.97 ha/person. The labor income farm families owners and tenants in average Rp. 1,199,408.33/month, only for farmers or tenants only (revenue sharing system) Rp. 599,704.17/month, while for farm workers is Rp. 198,148.15 per month. Production capacity for technical irrigated rice on average is at 7.1 tonnes/ha persekali for rainfed crops whereas on average be at 5:12 tonnes / ha persekali harvest. For the consumption needs of farmers for a decent life in general on average are in USD. 6.8085 million per year, equivalent to 801 kg of rice. While the strategy suggest that farmers' welfare can be increased is defensive. In this research, the expected policy implications that business activities had pani paddy rice is still heavily influenced by natural factors and little influenced by the availability of technical irrigation, for him it takes concrete steps from the government in the form of special programs and subsidies that prosperous rice farmers